Equalization advantages of OFFH-CDMA over WDM in EDFAs - Fouli, K.; Rusch, L.A. (IEEE photonics technology letters, 2005)
The gain of an erbium-doped fiber amplifier (EDFA) is in general wavelength-dependent, leading to different amplification levels among wavelength-division-multiplexing (WDM) channels. The use of optical fast frequency-hopped code-division multiple-access (OFFH-CDMA) offers a natural diversity of wavelength, and therefore gain, thus eliminating the requirement of an equalization stage to achieve flat gain on all channels. Computer simulations are developed to analyze and compare the EDFA equalization performance of these two transmission approaches (code-division multiplexing and WDM), especially in situations where the EDFA operating point is subject to change (e.g., channel add-drop, packet-switching environment). We find that WDM requires an equalization stage that fails when traffic characteristics shift, whereas, OFFH-CDMA presents the advantage of more robust, hence truly dynamic, gain equalization.